1995
DOI: 10.1111/j.1528-1157.1995.tb01672.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ex Vivo Magnetic Resonance Imaging to Detect Onset of Vigabatrin‐Induced Intramyelinic Edema in Canine Brain

Abstract: Vigabatrin (VGB) causes intramyelinic edema (microvacuolation) in brain of dogs and rodent, which has encouraged development of noninvasive methods to monitor for this effect during clinical trials. We report the qualitative ex vivo magnetic resonance imaging (MRI) changes observed in a neuropathology study in dogs to detect time of onset and regression of VGB-induced intramyelinic edema. Beagles were randomly assigned to 18 groups of 6 dogs per group and administered vigabatrin orally (p.o.) at a dose of 300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 15 publications
1
31
0
Order By: Relevance
“…The MR imaging signal intensity increased with the duration of the treatment and normalized 16 weeks after the drug was discontinued. 4 Myelin vacuolation has been reported in the myelinated white matter tracts of mice exposed to vigabatrin. 2 Further study of rats that have been treated with vigabatrin showed lesions in the cerebellar white matter and increased T2 relaxation on MR imaging, which correlated with microvacuolation on postmortem examination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MR imaging signal intensity increased with the duration of the treatment and normalized 16 weeks after the drug was discontinued. 4 Myelin vacuolation has been reported in the myelinated white matter tracts of mice exposed to vigabatrin. 2 Further study of rats that have been treated with vigabatrin showed lesions in the cerebellar white matter and increased T2 relaxation on MR imaging, which correlated with microvacuolation on postmortem examination.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized placebo-control study of 108 dogs given vigabatrin for Յ12 weeks demonstrated myelin vacuolation in the thalamus, hypothalamus, and fornix on histology 4 -5 weeks after treatment. 4 The ages of the dogs were not stated. MR imaging changes were present in these animals several weeks after histologic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vigabatrin, however, has not been a consistently helpful therapeutic for these patients, and there have been many reports of lack of effect or, worse, worsening of symptoms ranging from seizure control to alertness. Further, there have been concerns regarding vigabatrin, resulting thus far in absence of U.S. Food and Drug Administration approval, initially because of intramyelinic edema and white matter vacuolation in rats and dogs (22,148,153). In clinical trials, 30% of patients treated with vigabatrin for epilepsy report visual field defects after 1 year of treatment (103,181,190).…”
Section: Treatment Strategies and Challengesmentioning
confidence: 99%
“…Increased signal on T,-weighted images and histologic changes of IME were closely correlated. In dogs, regions with IME demonstrated increased signal on T,-weighted images and decreased signal on T, -weighted images (16,48). The development of the T, signal abnormality followed the time-course and anatomic distribution of pathologic changes.…”
Section: Magnetic Resonance Imaging In Animalsmentioning
confidence: 99%